The difference in energy metabolism between barrows and gilts and its effect on fat deposition and carcass quality - Diemont, Dirk Lusk Pierre (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1992.